Exposure to urban green spaces and mental health during the COVID-19 pandemic: evidence from two low and lower-middle-income countries - Patwary, Muhammad Mainuddin; Bardhan, Mondira; İnan, Hüseyin Ertan and Browning, Matthew H. E. M. and Disha, Asma Safia and Haque, Md. Zahidul and Helmy, Mai and Ashraf, Sadia and Dzhambov, Angel M. and Shuvo, Faysal Kabir and Alam, Md. Ashraful and Billah, Sharif Mutasim and Kabir, Md. Pervez and Hossain, Md. Riad and Azam, Md. Golam and Rahman, Md. Mijanur and Swed, Sarya and Sah, Ranjit and Montenegro-Idrogo, Juan J. and Bonilla-Aldana, D. Katterine and Rodriguez-Morales, Alfonso J. (Frontiers in Public Health, 2024)
Introduction The COVID-19 pandemic has had a significant impact on mental health globally, with limited access to mental health care affecting low- and middle-income countries (LMICs) the most. In response, alternative strategies to support mental health have been necessary, with access to green spaces being a potential solution. While studies have highlighted the role of green spaces in promoting mental health during pandemic lockdowns, few studies have focused on the role of green spaces in mental health recovery after lockdowns. This study investigated changes in green space access and associations with mental health recovery in Bangladesh and Egypt across the pandemic. Methods An online survey was conducted between January and April 2021 after the first lockdown was lifted in Bangladesh (n = 556) and Egypt (n = 660). We evaluated indoor and outdoor greenery, including the number of household plants, window views, and duration of outdoor visits. The quantity of greenness was estimated using the normalized difference vegetation index (NDVI). This index was estimated using satellite images with a resolution of 10x10m during the survey period (January-April 2021) with Sentinel-2 satellite in the Google Earth Engine platform. We calculated averages within 250m, 300m, 500m and 1000m buffers of the survey check-in locations using ArcGIS 10.3. Multiple linear regression models were used to evaluate relationships between changes in natural exposure and changes in mental health. Results The results showed that mental health improved in both countries after the lockdown period. People in both countries increased their time spent outdoors in green spaces after the lockdown period, and these increases in time outdoors were associated with improved mental health. Unexpectedly, changes in the number of indoor plants after the lockdown period were associated with contrasting mental health outcomes; more plants translated to increased anxiety and decreased depression. Refocusing lives after the pandemic on areas other than maintaining indoor plants may assist with worrying and feeling panicked. Still, indoor plants may assist with depressive symptoms for people remaining isolated. Conclusion These findings have important implications for policymakers and urban planners in LMICs, highlighting the need to increase access to natural environments in urban areas to improve mental health and well-being in public health emergencies.